Iowa Birdline update, March 29, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for March 29, 1993. Highlights of the update include sightings of the continued presence of a Black-throated Sparrow, Gyrfalcon, Snowy Owl and Sandhill Crane. Also included are handwritten notes for the next week's update with sightings of several returning birds, the Common Loon, Eared and Horned Grebes, Bonaparte's Gull and a Tree Swallow. Epson - sheet feed/flatbed